THE ANGRY YOUNG MEN MOVEMENT: POST-WAR LITERARY REBELLION AND ITS CULTURAL IMPACT - Chinakov Abdulahad Mo‘minjon ugli (TADQIQOTLAR, 2025)
The "Angry Young Men" movement emerged in post-World War II Britain as a cultural  and  literary  phenomenon,  capturing  the  frustrations  and  aspirations  of  a generation  disillusioned  by  traditional  values  and  societal  constraints.  This  study examines the historical context, defining characteristics, and enduring legacy of the movement, emphasizing its impact on literature and broader cultural discourse.